COVID‐19 and the US Safety Net. (30th November 2020) - Moffitt, Robert A.; Ziliak, James P.
Abstract: We examine trends in employment, earnings and incomes over the last two decades in the United States, and how the safety net has responded to changing fortunes, including the shutdown of the economy in response to the COVID‐19 pandemic. The US safety net is a patchwork of different programmes providing in‐kind as well as cash benefits, and it had many holes prior to the pandemic. In addition, few of the programmes are designed explicitly as automatic stabilisers. We show that the safety net response to employment losses in the COVID‐19 pandemic largely consists only of increased support from unemployment insurance and food assistance programmes, an inadequate response compared with the magnitude of the downturn. We discuss options to reform social assistance in the United States to provide more robust income floors in times of economic downturns.